10th Anniversary of Processes (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The aim of this reprint is to show the main lines of research in green environmental processes in recent years. As in previous years, there is a clear trend in current environmental research towards biological processes for the treatment of water, wastewater, waste, and soil; however, pyrolysis and biochar have emerged with force. Several papers highlighting the role of this thermal treatment and the uses of biochar as its main product are included in the review as an emerging line of research that is gaining in importance. Biochar-based processes are gaining popularity in key environmental technologies involving bioremediation, decontamination, and decarbonisation.